Integrating 3Rs approaches in WHO guidelines for the batch release testing of biologicals. (November 2021) - Lilley, Elliot; Isbrucker, Richard; Ragan, Ian; Holmes, Anthony
Abstract: Animal testing has long been integral to the development of biologicals, including vaccines. The use of animals can provide important information on potential toxicity, insights into their mechanism of action, pharmacokinetics and dynamics, physiologic distribution, and potency. However, the use of these same methods is often adopted into the post-licensure phase of the product life cycle for the monitoring of product qualities, such as potency or safety, as part of their routine batch release. The UK National Centre for the Replacement, Refinement, and Reduction of Animals in Research (NC3Rs) and the World Health Organization (WHO) are collaborating on a project to review animal-based testing methods described in WHO manuals, guidelines and recommendations for biologicals to identify where updates can lead to a more harmonised adoption of 3Rs principles (i.e. Replacement, Reduction, and Refinement of animal tests) in batch release testing requirements. An international working group consisting of more than 30 representatives from pharmaceutical and biotechnology companies, national control laboratories and regulatory bodies is performing this review. This project aims to address concerns about inconsistencies in the guidance for the scientifically justified use of animal methods required for the post-licensure quality control and batch release testing of biologicals, and the near absence of recommendations for the application of 3Rs principles within the relevant guidelines. Improved adoption of 3Rs principles and non-animal testing strategies will help to reduce the delays and costs associated with product release testing and help support faster access to products by the global communities who need them most urgently.